PENGARUH COVID-19 TERHADAP REAKSI PASAR MODAL INDONESIA (STUDI KASUS PADA INDEKS SAHAM LQ-45) - Suwarto Suwarto; Shinta Wulandari (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this study is to determine the effect of a COVID-19 event on the reaction of the Indonesian capital market (case study on the LQ-45 stock index). To test the market reaction, the researcher uses Abnormal return and trading volume activity variables to test an event that is happening.Based on the results of the significance test using the one-sample t-test and the one-sample Wilcoxon signed rank test and different tests using the paired sample t-test and the Wilcoxon signed rank test on abnormal return and trading volume activity above, the researcher concluded that the test on abnormal return and trading volume activity before and after the announcement of the COVID-19 event on March 2, 2020, experienced a significant change, meaning that abnormal return and trading volume activity, which means that there is a significant influence on the COVID-19 event on the reaction of the Indonesian capital market (Study The Case in the LQ-45 Stock Index).